Pengembangan Nilai-Nilai Kearifan Lokal Sebagai Bentuk Transformasi Pendidikan Agama di STAHN Mpu Kuturan Singaraja - Suwindia, I Gede; Kurnia Wati, Ni Nyoman (Jayapangus Press, 2023)
This study aims to preserve the values ​​of local wisdom in general, and to produce indicators and instruments for the value of local wisdom in particular. The values ​​of local wisdom were developed in this study due to the rapid advancement of technology and in order to realize the vision of the university itself. This study uses a Research and Development (R&D) model with a 3D development model, namely the define, design, and develop stages. The research subjects for the development of local wisdom values ​​were 2 experts or expert practitioners in their fields and a limited trial of this product using 20 respondents. There are 2 (two) data collection methods used in this study, namely the document study method and the questionnaire method. The data analysis method used in this research is descriptive qualitative. Content validation of indicators of local wisdom values ​​used the analysis of two experts, then analyzed using the Gregory technique. The limited test by practitioners in this study used 20 respondents from steakholders at STAHN Mpu Kuturan Singaraja. The results of the limited test on the value of local wisdom were analyzed using the average score of the respondents. To determine the quality of each local wisdom value, the average score of the respondents was converted using the criteria for the ideal mean (Xi) and the ideal standard deviation (SDi) on a scale of five. The results showed that the product indicator for each local wisdom value was 1, so it was in the very high category. And the average score of each local wisdom value is also in the very high category. This shows that the product produced in this study is worthy of being used as an instrument to measure the values ​​of local wisdom in transforming religious education, especially in STAHN Mpu Kuturan Singaraja.